Os coletivos criminais de Porto Alegre entre a “paz” na prisão e a guerra na rua - Rodrigues, Marcelli Cipriani (2019)
In 2016 there were several homicides in certain areas of Porto Alegre, in what seemed a domino effect. From the beginning of the 1980’s until 2018, that was the year with the largest number of homicides, and Porto Alegre became the most violent capital in Brazil. Some aspects of these deaths suggest that there was some trend happening in the relationship among criminals. At the same time, in the Public Jail of Porto Alegre – the main prison in the state of Rio Grande do Sul, where several different criminal organizations coexist – homicides in the prison population had considerably dropped. Generally, the idea that initiated this research is the relation between criminal organizations and lethal violence. We have analyzed the social universe in that prison as well as in some neighborhoods in the city to try to understand the mix of social relationships that gave rise to the coexistence of a “pacification” process in prison and the recent spree of deaths outside its walls – an also investigating the presence of violence in the actions of members of the criminal factions. We have done interviews with people with different social roles: inmates, police officers, justice system workers, juvenile offenders (both in prison and on probation) and people living in the outskirts of the city. We have also used data from the observation of drug selling outlets and online groups from neighborhoods with a strong presence of criminal organizations, from the systematization of informal conversations and from document analysis. In the first chapter we review the history of the forming of “Southern Phalanx” [Falange Gaúcha] in the Public Jail – the first criminal organization in Porto Alegre – whose rise was accompanied by incessant instability such as rebellions in jail and homicides among inmates, until the present accommodation of these internal social relations that resulted in the “pacification” of the prison. This analysis was done taking into consideration the police tactics used to maintain the order in the prison, the changes perceived in the drug outlets, in legislation and in incarceration. On the second chapter, we tried to reconstitute what the interviewees called “the war” and to understand the relations that resulted in this period of crime in Porto Alegre. This reconstitution comprehends the transformations perceived in the traffic rings in the past few years, especially the alliances between criminal groups and a mechanism of support and reciprocity among criminal factions. We could see that with “the war” and the negotiations inside the jail, crime has polarized around two large alliances – “Bullet Face” [Bala na Cara] and “Antibullet” [Antibala] – that reorganized local micro conflicts and criminal groups in allies and antis. The reorganization of these relationships has impacted the urban circulation of youths from the periphery, it has accentuated the construction of collective identities in opposition to the antis and it has altered the patterns of violence, which became much more extreme and with a symbolic character, with the goal to terrorize the antis. With violent attacks and the “hunt” of the antis, that were designed more to weaken the position of the enemy faction and less to punish specific individuals, the number of potential victims has risen and it started a lethally violent cycle of retaliation. We could also identify that the “pacification” in prison was not a consequence of the alienation of violence as a structuring device in the groups, but a result of agreements with agents of the state and different criminal groups that took into consideration the interests of all the parties involved, and with the idea in mind that there is a war, but it should be fought on the streets. So, “peace” was a result of a negotiation that prioritized the benefits of the free flux into and out of the prison walls, which gave rise to the substitution of the logic of gaining terrain inside prison to the logic of managing the antis – using space, autonomy and power from the inside to strengthen their power outside,on the streets.